Influence of Background Noise Produced in University Facilities on the Brain Waves Associated With Attention of Students and Employees. (September 2017) - Trista´n-Hernández, E.; Pav´on-García, I.; Campos-Cantón, I.; Ontaño´n-García, L. J.; Kolosovas-Machuca, E. S.
As a consequence of noise exposure, lack of attention badly affects directly the academic and work performance. The study of the brain and the waves that it produces is the most objective way to evaluate this process. Attentional improvement is associated with increases of the amplitude in both beta and theta bands. The objective of this work is to study the influence of background noise produced inside university facilities on changes in the cerebral waves related to attention processes (beta 13–30 Hz and theta 4–7 Hz). Volunteers were asked to perform a specific task in which attention was involved. This task was performed in both silent and noisy conditions. To evaluate the cerebral activity of volunteers during the development of the test, measurement of spontaneous activity (electroencephalogram) was developed. The results show significant decreases in both beta and theta frequency bands under background noise exposure. Since attentional improvement is related to an increment on amplitude of both beta and theta bands, it is suggested that decreases on amplitude of these frequency bands could directly be related to a lack of attention caused by the exposure to background noise.